Asuhan Keperawatan Pada Tn. T Dengan Resiko Perilaku Kekerasan - Siti Salamah; Sri Nyumirah (AKPER Pasar Rebo, 2018)
Violent behavior is a form of behavior that injures a person physically and psychologically. The impact of violent behavior by clients on themselves is that they can injure themselves, aggressive actions aimed at injuring themselves or killing others, damaging the environment, throwing glass, tiles and everything in the environment. Based on the impact of Violence Behavior above, the role of nurses is needed in performing nursing care, namely nurses play a role in promotive, preventive, curative and rehabilitative roles. Nursing care is carried out to conduct an assessment until evaluation of the client's violent behavior. Nursing care is carried out by means of interviews, both to clients, nurses and families, nursing actions are carried out directly on the client by assisting nurses. The client experiences violent behavior feeling irritated because his mother talked a lot at home. Nursing diagnoses that can be found in clients are low self-esteem, self-care deficits, risk of violent behavior, risk of sensory perception disorders: hallucinations, social isolation. Nursing planning is carried out in accordance with Hospital standards. Client nursing evaluation can be seen in the client being able to control violent behavior by breathing deeply as well as throwing a pillow / mattress, taking medication regularly, expressing, asking and rejecting verbally and spiritually namely dhikr and prayer. Other capabilities that the client achieves is that the client is able to control hallucinations, which arise, the client is able to get acquainted with 1 person or more, and the client can maintain his cleanliness.